84.9k views
1 vote
Solve the following formula for H. r=n/2(b+H)

User Marek Raki
by
5.4k points

2 Answers

3 votes

Answer:

See below.

Explanation:

What you wrote means:


r = (n)/(2)(b + H)

If that is what you meant, then the answer is:


(2r)/(n) = b + H


H = (2r)/(n) - b

On the other hand, if this is what you meant:


r = (n)/(2(b + H))

then the answer is:


2r(b + H) = n


2rb + 2rH = n


2rH = n - 2rb


H = (n - 2rb)/(2r)

User Asaf Chertkoff
by
6.0k points
5 votes

Answer:

Explanation:


(n)/(2)(b + H) = r\\\\b +H = r * (2)/(n)\\\\b + H = (2r)/(n)\\\\H = (2r)/(n) - b

User Daniel Harms
by
5.9k points